2018
DOI: 10.1093/asj/sjy166
|View full text |Cite
|
Sign up to set email alerts
|

What is “Nonbinary” and What Do I Need to Know? A Primer for Surgeons Providing Chest Surgery for Transgender Patients

Abstract: Chest surgery for non-binary patients comprises a significant proportion of our transgender surgery practice, and surgeons providing affirming care should be familiar with the unique characteristics and treatment options for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Only one study addressing health outcomes related to medical interventions for NBGQ individuals was found. Among 458 patients undergoing gender-affirming chest surgery, Esmonde et al (2018) found that 13% ( N = 58) were NBGQ, all FAAB. Among them, 56% ( N = 33) completed the post-operative questionnaire.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study addressing health outcomes related to medical interventions for NBGQ individuals was found. Among 458 patients undergoing gender-affirming chest surgery, Esmonde et al (2018) found that 13% ( N = 58) were NBGQ, all FAAB. Among them, 56% ( N = 33) completed the post-operative questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the only study analyzing the effects of medical interventions on health of NBGQ individuals (i.e., third research question) found that NBGQ FAAB individuals, contrary to the belief that they would not need to medically affirm their gender, improved their quality of life and health after chest surgery (Esmonde et al, 2018). This result is in line with previous studies which found that both hormonal treatment (e.g., Newfield et al, 2006) and chest surgery (e.g., Agarwal et al, 2018) commonly improved the quality of life and well-being of female-to-male transgender individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of dysphoria, improvement of body image and confidence following mastectomy affected sexual relationships positively. 38,183,184 Removal of the Female Sexual Organs Evidence. Indications for hysterectomy include persistent blood loss, dysphoric feelings, unwanted discharge or lubrication, and within the context of GAS with urethral lengthening.…”
Section: Surgical Procedures For Masculinizing Gasmentioning
confidence: 99%
“…Reduction of dysphoria, improvement of body image and confidence following mastectomy affected sexual relationships positively. 38 , 183 , 184 …”
Section: Surgical Procedures For Masculinizing Gasmentioning
confidence: 99%
“…The US Transgender Survey (2015) reported that only 25% of 27, 000 respondents had undergone a gender-affirming surgery [3]. Additionally, people with non-binary identities may not identify as either a man or a woman and may undergo gender-affirming surgery [4].…”
Section: Introductionmentioning
confidence: 99%